The Effectiveness of Group Counseling Using Self-Talk Techniques to Reduce Procrastination in Students Experiencing Post-Earthquake Trauma - Dona Fitri Annisa; Lira Erwinda; Yuda Syahputra (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Post-disaster trauma, such as that experienced after the earthquake in Cianjur, can lead to psychological issues among students, including academic procrastination. Interventions are needed to help students regain focus and motivation in their learning. Objective: This study aimed to determine the effectiveness of group counseling using self-talk therapy techniques in reducing academic procrastination among students during the post-earthquake traumatic period at SMPN 03 Cianjur, West Java. Method: The research was conducted in 2022 using a pre-experimental design with a one-group pretest-posttest approach. Data were collected using a procrastination scale administered before and after the intervention. The Wilcoxon Signed Ranks Test was used to analyze the data. Result: The analysis showed a significant reduction in students' procrastination scores after the implementation of group counseling with self-talk therapy techniques, indicating a positive effect of the intervention. Conclusion: Group counseling using self-talk therapy techniques is effective in reducing academic procrastination among students affected by earthquake trauma. Contribution: This study contributes to the development of trauma-informed counseling practices by providing evidence of the effectiveness of self-talk techniques in group settings, offering a valuable approach for school counselors in post-disaster recovery programs.